Características da lenha produzida na região da quarta colônia de imigração italiana do Rio Grande do Sul - Darci Alberto Gatto; Elio José Santini; Clovis Roberto Haselein; Miguel Antão Durlo (Ciência Florestal, 2003)
This research was carried out with the objective of evaluating the firewood quality produced in the 4th Colony of Italian Immigration of Rio Grande do Sul taking into account the conversion factor from stacked to cubic meter, moisture content, basic density and fuel value of the wood. The conversion factor, important in estimating the solid volume, ranged from 0,61 for eucalypt wood to 0,56 for native species. The wood basic density found for eucalypt was 0,44 g/cm3 compared to 0,46 g/cm3 for native species, assorting them as slightly dense wood. The estimated heat of combustion for the wood equilibrium moisture content of the region was 1915 and 2002 kwh/m3, respectively, for eucalypt and native firewood. However, 13,6% of these values are lost because the wood is burned with an average moisture content of 32%. These results indicate the need of a more careful stacking and drying of the firewood, what would lead to a decrease in energy losses that happens when moist material is burnt.